(untitled) (Physical Education, Health and Social Sciences, 2025)
Teenage pregnancies present significant health and psychological challenges, particularly in underdeveloped and populated region like Faisalabad District, Punjab, Pakistan. The study is aimed to evaluate psychological complications through semi structured interviews and observation methods through longitudinal strategy that may arise in fetuses due to maternal stress, inadequate medical care, and socio economic factors associated with adolescent pregnancies. Maternal stress and anxiety during the production period have been linked to altered fetal brain development, increasing the risk of cognitive and emotional disorders in newborns. Additionally, poor nutrition, lack of medical care, and social stigma contribute to developmental delays, low birth weight, and higher incidents of mental health disorders in the later life. This is suggested to tackle the targeted health program urgently, mental health care through psychotherapy, and educational initiatives to mitigate the risk associated with teenage pregnancies in Faisalabad. By addressing these issues, the neonatal health outcome and prolonged psychological burden on both mother and child can be improved by health initiatives and education.